DISTRIBUTION OF CLICK BEETLES AND THE DEVELOPMENT OF CONTROL MEASURES IN POTATO FIELDS OF THE REPUBLIC OF ARMENIA - Terlemezyan, H.L.; Sargsyan, M.A.; Harutyunyan, H.R.; Mkrtchyan, H.N. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
The studies were conducted at the Aragatsotn region of the Republic of Armenia during the years 2021-2024. Four species of click beetles (family Elateridae) belonging to the order Coleoptera of the class Insecta were recorded. The most widespread species was the sowing click beetle (Agriotes sputator L.), making up 56%. The steppe click beetles (Agriotes gurgistanus Fald.) accounted for 25% of the total population. The striped (Agriotes lineatus L.) and dark (Agriotes obscurus L.) click beetles were relatively less common, constituting 14% and 5%, respectively. Based on the analysis of the damage caused by wireworms to the tubers of different potato varieties it can be concluded that the Impala and Arizona varieties are more resistant to the phytophagous pest. These varieties are recommended for cultivation in potato farms.   Nuprid (0.2 L/t), Kruiser (0.2 L/t), and Force (15 kg/ha) demonstrate high biological efficacy against wireworms, showing effectiveness comparable to the standard variant, Prestige (1.0 L/t).